Quadriceps and Hamstring Muscle Strength in Elderly based on Lifestyle - Sze Lyn, Pang; Moeliono, Marina A.; Dewi, Sumartini (Althea Medical Journal, 2017)
Background: Studies have shown that muscle strength will decline with aging and inactivity, with 1% to 3% loss of muscle strength each day. Nevertheless, different lifestyles have different effect on muscle strength. This study was conducted to analyze the differences in quadriceps and hamstring muscle strength in elderly from 60â79 years olds according to lifestyle.Methods: A cross-sectional study was conducted from September to November 2015. The subjects were 31 older persons from community who voluntarily participated the research procedure and were divided into 2 groups, active group and sedentary group according to International Physical Activity Questionnaire (IPAQ). Quadriceps and hamstring muscle strengths were measured using the push and pull dynamometer. The collected data were analyzed using the Wilcoxon rank sum test and the unpaired t-test. Results: This study discovered that the mean difference in hamstring muscle strength was 6.09 Â± 0.70, p< 0.001; median difference in Quadriceps muscle strength was 5.00 (13.00, 6.50), p<0.001. Conclusions: There is a higher Quadriceps and Hamstring muscle strength in elderly active lifestyle compared to elderly sedentary lifestyle.Â Â